Formulation and Evaluation of Body Scrub Cream Containing Ethanol Extract of Black Cumin Seeds (Nigella sativa L.) and Coffee Grounds (Coffea arabica L.) as Anti-aging - Hasibuan, Poppy Anjelisa Zaitun; Sumaiyah, Sumaiyah; Siregar, Dedek Harianti (Talenta Publisher, 2022)
Cosmetics are now mandatory for most women. Various natural ingredients have now been used as basic ingredients for beauty treatments. This study aimed to formulate and determine the effectiveness of body scrub cream preparations containing ethanolic extract of N. sativa and coffee grounds as antiaging. The skin antiaging was divided into five formulas: F0 (cream base), F1 (coffee ground 5%), F2 [coffee ground 5% + Ethanol Extract of N. sativa (EENS) 2%], F3 (coffee ground 5% + EENS 3.5%) and F4 (coffee ground 5% + EENS 5%). The body scrub cream preparations were subjected to organoleptic, homogeneity, emulsion type, and pH evaluation. The irritation test and antiaging activity were evaluated by using a skin analyzer. The body scrub was stable in 12-week storage. The result showed that there was no irritation on the volunteers’ skin. The body scrub cream with the highest antiaging activity was the F4 formula. It showed 9.6% for increasing skin moisture, 17.68% for increasing skin smoothness, 11.42% in reducing the size of pores and 12.84% in reducing the number of spots.